2021
DOI: 10.1177/1758835921998586
|View full text |Cite
|
Sign up to set email alerts
|

Relugolix: a novel androgen deprivation therapy for management of patients with advanced prostate cancer

Abstract: Androgen deprivation therapy (ADT) is the foundation of treatment for patients with locally advanced, recurrent and metastatic prostate cancer, most commonly using luteinizing releasing hormone (LHRH) agonists. More recently, a new approach to ADT has emerged with the development of gonadotropin-releasing hormone (GnRH) antagonists, which aim to overcome some of the potential adverse physiologic effects of LHRH agonists. This article focuses on the newest GnRH antagonist, relugolix – a once-daily treatment and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Another area of interest for future study is on intermittent versus continuous relugolix treatment. Indeed, in the context of intermittent ADT for prostate cancer, the once-daily dosing, the rapid onset of action, and the apparent more rapid testosterone recovery associated with relugolix could potentially help facilitate more precise or targeted ADT [ 27 ]. The testosterone recovery observed with relugolix may have other clinically meaningful benefits, for example for men receiving a short course of ADT, or for men unable to tolerate adverse effects of testosterone suppression [ 12 ].…”
Section: Place Of Relugolix In the Management Of Advanced Prostate Ca...mentioning
confidence: 99%
“…Another area of interest for future study is on intermittent versus continuous relugolix treatment. Indeed, in the context of intermittent ADT for prostate cancer, the once-daily dosing, the rapid onset of action, and the apparent more rapid testosterone recovery associated with relugolix could potentially help facilitate more precise or targeted ADT [ 27 ]. The testosterone recovery observed with relugolix may have other clinically meaningful benefits, for example for men receiving a short course of ADT, or for men unable to tolerate adverse effects of testosterone suppression [ 12 ].…”
Section: Place Of Relugolix In the Management Of Advanced Prostate Ca...mentioning
confidence: 99%
“… 1 , 2 Relugolix, compared to leuprolide, has shorter time to testosterone suppression, higher rate of sustained testosterone suppression, and faster testosterone recovery upon therapy completion. 3 , 4 We describe, to our knowledge, the first case of a moderate skin rash in a male patient undergoing relugolix treatment for metastatic prostate cancer.…”
Section: Introductionmentioning
confidence: 92%
“…As detailed earlier in this paper, many researchers have found that GnRH antagonists like degarelix have fewer associated CV adverse events than their agonist counterparts [ 24 , 26 , 29 , 31 ]. Relugolix may be given additional consideration due to recent clinical trial data showing very low associated CV risk [ 68 , 69 ]. Androgen synthesis inhibitors (i.e., abiraterone) and androgen receptor antagonists (i.e., enzalutamide) have become key agents for castration sensitive and resistant PCa; however, they also can carry increased CV risk, and clinicians should take appropriate measures to monitor and modify their CV risk factors.…”
Section: Risk Managementmentioning
confidence: 99%